ENGLISH AS A PRIVILEGED LANGUAGE FOR STUDYING - Axtamova, Nasiba; Gafurova, Dilfuza Jabborovna (INTERNATIONAL CONFERENCE DEDICATED TO THE ROLE AND IMPORTANCE OF INNOVATIVE EDUCATION IN THE 21ST CENTURY, 2022)
This article discusses the importance of teaching English as a foreign language for the further integration of our Republic into the world community.